U Use Of Contraception To Increase Knowledge Of Reproductive Health In Couples Of Fertilizing Age (Prosiding Seminar Nasional Masyarakat Tangguh, 2024)
Family planning is an effort to regulate the number of births. Indonesia's health profile data in 2016 found 6,663,156 PUS which were new family planning, active family planning coverage nationally was 36,306,662 participants (74.80%). Meanwhile, active family planning coverage in South Kalimantan in 2016 was 589,920 participants (76.99%). The largest number of contraceptive users were birth control pills at 44.86%, injections at 41.61%, and implants at 7.78%, and other methods at 0.3%. The target of this community service is the PUS in RW03 Kindingan Health Center, totaling 19 people. The health education results showed that the majority of PUS education was high school, 63%, the majority of PUS did not use contraception, namely 53%, the highest number of PUS children was 3 people, namely 40%. The pretest average was 66 and the posttest was 85, meaning there was an increase in PUS knowledge about the use of hormonal contraception